Farm-level adoption and impact of agricultural technology: the case of Russian wheat aphid resistant cultivars in South Africa - Marasas, Carissa N.; Anandajayasekeram, P.; Millard, S.; Van Rooyen, C. J. (2005)
This paper emphasizes adoption and impact studies as tools to assess the benefits of agricultural technologies, and to provide feedback for further technology development. The findings are reported of a study undertaken to describe the adoption and impact of Russian wheat aphid (RWA) resistant cultivars developed by the South African Agricultural Research Council. The analyses employed farm-level data from surveys conducted in 1997 in the Central and Eastern Free State of South Africa. Rapid adoption of the cultivars was demonstrated since their first release in 1993. The area sown to the cultivars increased from 3% in 1993 to 46% in 1997. Correlation and multiple regression analyses suggested that adoption of the cultivars was influenced by the farmer's educational level, wheat area, and experience with RWA; the quality grades realized by resistant cultivars; and the combined weighted average yield of resistant and susceptible cultivars. Economic analyses using partial budgets indicated that resistant cultivars generated incremental net benefits ranging between 140 and 329 Rands/ha in 1997 prices. The findings demonstrate that various factors apart from pest resistance also influenced the farmers' decisions to adopt RWA resistant cultivars, and underline the importance of farm-level data in agricultural research and extension.